(untitled) (Scientific journal of the Fergana State University, 2025)
The article deals with the poetics of gestures in the short story of the great Austrian writer Stefan Zweig “Twenty-Four Hours in the Life of a Woman”. In the novella the tragedy of a young man obsessed with gambling is masterfully depicted. The author employs artistic details to achieve a dynamic portrayal and to reveal psychological aspects of the human soul through the motif of “hands”. For instance, the text notes how “the green table is surrounded by numerous hands, each representing a distinct character”. These hands serve as a metaphor for the inner state of individuals, highlighting their nervousness and anxiety. Research indicates that in literary works, the expression of human psychology through gestures and facial expressions plays a significant role. As a result, the author illustrates how observing hand movements enables the main character to understand the inner worlds of those around her. This article analyzes the issue of artistic psychological realism in Stefan Zweig’s novella “Twenty-Four Hours in the Life of a Woman”. The author reveals the complexity of human psychology, particularly that of women, through unique details and gestures. Using the example of a young man’s tragedy driven by gambling addiction, Zweig profoundly illuminates the inner world of the characters and their psychological states through the depiction of hands. The article demonstrates the significance of artistic psychological realism and Zweig’s stylistic mastery while discussing the role of psychological analysis in literature.